Known-plaintext attack on a joint transform correlator encrypting system - Barrera Ramírez, John Fredy (2010)
We demonstrate in this Letter that a joint transform correlator shows vulnerability to known-plaintext attacks. An unauthorized user, who intercepts both an object and its encrypted version, can obtain the security key code mask. In this contribution, we conduct a hybrid heuristic attack scheme merge to a Gerchberg–Saxton routine to estimate the encrypting key to decode different ciphertexts encrypted with that same key. We also analyze the success of this attack for different pairs of plaintext–ciphertext used to get the encrypting code. We present simulation results for the decrypting procedure to demonstrate the validity of our analysis.–Saxton routine to estimate the encrypting key to decode different ciphertexts encrypted with that same key. We also analyze the success of this attack for different pairs of plaintext–ciphertext used to get the encrypting code. We present simulation results for the decrypting procedure to demonstrate the validity of our analysis.